THE TEMPERATURE DISTRIBUTION IN THE EARTH’S CRUST OF MODERN AND PRECAMBRIAN ACTIVE REGIONS - GORDIENKO , V.; GORDIENKO , I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Temperatures of the depths have no differences between Precambrian and recent meanings. Activization happens ander the temperatures that are differ only inside boundaries of personal distinctions of the tectonic blocks.